Buried Impact Features on Mercury as Revealed by Gravity Data. Issue 11 (8th November 2018) - Qingyun, Deng; Fei, Li; Jianguo, Yan; Zhiyong, Xiao; Rodriguez, J.Alexis P.
Abstract: Gravity data provide information about the internal mass distribution of celestial bodies. The latest gravity field model of Mercury, HgM007, has a higher spatial resolution than previously published gravity models, allowing smaller crustal structures to be resolved. In this study, a global free‐air gravity anomaly grid of Mercury was derived from the HgM007 gravity model using the spherical expansion method, and a Bouguer anomaly map was calculated based on the free‐air gravity and topography data. We used this gravity model to search for quasi‐circular Bouguer anomalies (QCBAs) larger than ∼109 km in diameter within the Northern Smooth Plains (NSP) of Mercury, where the resolution of the gravity data is the highest. Assuming that these QCBAs were correlated with mantle uplifts caused by ancient buried impact structures, we applied the prism rectangular shape model and the Markov chain Monte Carlo inversion method to determine the subsurface structure of these QCBAs. Four ancient buried basins, not clearly visible in the surface topography, were detected. We estimated the crustal thickness ratios and original rim‐to‐rim diameters for these four impact basins, based on empirical cratering scaling laws, finding that the thickness of the infill lava within the NSP might be 5 times larger than previously believed and the ancient terrain beneath the NSP might be older than previously thought. Plain Language Summary: Impact basins are generally characterized by two or more concentric rings in the topography. The mass concentration beneath it make impact basins always characterized with gravity high in a gravity anomaly map. The subsurface mass concentration structures take a long time to reach the equilibrium state. Therefore, the gravity data can be used to identify buried impact basins in terrestrial planets. In our work we used a novel Mercury gravity field model and digital elevation model to produce a topography‐corrected gravity map. By means of gravity inversion we located four buried impact basins with no topography features. We suggested that surfaces in these buried basins are more ancient than previously thought. Key Points: A novel Mercury gravity field model has enhanced its sensitivity to short‐wavelength signatures Four potential buried impact basins are identified from gravity inversion Surfaces beneath the Northern Smooth Plains are more ancient than previously thought